Geographic Information System for Mapping Deployment Areas Dengue Fever in Umalulu District - Rewa Ngguku, Arbin; Pingky Alfa Ray Leo Lede; Erwianta Gustial Radjah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Dengue fever is a disease caused by the dangue virus, causing serious health problems, especially in Umalulu sub-district, East Sumba Regency which has an area of 307.90 km2 and consists of 10 villages, each of which has an impact on dengue cases. This study aims to map the area of the spread of dengue fever in real time in Umalulu sub-district using a Geographic Information System (GIS), which is currently experiencing the problem of an increase in the number of dangue hemorrhagic fever cases and assistance that has not been targeted. The research method used is Waterfall, which follows the stages of planning, data collection, system analysis and design, implementation, and maintenance. Based on black box testing, this research succeeded in producing a web-based GIS that maps the dengue fever distribution areas in showing that the Lumbukore village is the area that has the highest number of cases with 12 and the Ngarukanoru village with the lowest area with 0 cases, with an average of many cases occurring in March and April of 2024 in Umalulu District, allowing users to analyze dengue disease distribution patterns provide recommendations for prevention and control measures for dengue disease more accurately and on target.